Hikmah Walimah Al-‘Ursy (Pesta Pernikahan) Dengan Kehormatan Perempuan Perspektif Hadits - Lia Laquna Jamali; Lukman Zain; Ahmad Faqih Hasyim (UIN Siber Syekh Nurjati Cirebon, 2016)
Walimah al-'ursy is one of a series of events in the process of marriage. Islam recommends to hold a feast al-'ursy after conducting the ceremony. It is very important and not to be underestimated, because walimah al-'ursy aligned with the honor of women. Based on that background to discuss hadith walimah al-'ursy. The assessment covered in this study include: the quantity and quality of the chain and honor traditions, the meaning and understanding of the traditions, and the relationship walimah al-'ursy with the honor of women. Data collection was referring to some source library (library research).The theory used in this research is the theory maani al-Hadith offered by Yusuf al-Qardawi. Based on the study of hadith walimah al-'ursy that: In terms of quantity included in the category of hadith ahad 'Aziz and in terms of quality category sahih li gairihi. Defining and understanding hadith walimah al-'ursy there are objective and important lessons in it as information to the public was the wedding and all the relatives and other relatives can come together to celebrate happiness and wish the best to live in harmony as a married couple.Â The connection between the meaning of the hadith walimah nowadays very closely with women's honor, because honor is very important both in terms of any case. At every wedding organized to implement the feastal-'ursy after the holding of the ceremony. Especially with the feast of al-'ursy to avoid the issue of marriage sirri commonly called marriage under the hand without recorded by the Marriage Registrar Officer and can lead to several negative outlook. So that it can drop the dignity and honor of women in particular.Â Keywords: Walimah al-'ursy, honor women